Growth and yield improvement of MR219 and Sri Malaysia 1 rice varieties employing targeted CO2 enrichment regimes - Sadiq, Salihi Mohammad (2021)
Rice (Oryza sativa L.) is one of the most important members of the Poaceae family as this crop has been the staple food for people in various nations, especially in Asian countries. Current climate changes and increasing carbon dioxide (CO2) concentration in the atmosphere have varying global impacts on crop performance. As CO2 is one of the limiting factors in photosynthesis, any addition of this gas can increase carboxylation activity, hence increases productivity and yield. Thus, this research was conducted to study the effects of elevated CO2 (eCO2) CO2 on rice seedlings' growth and establishment for MR219 and Seri Malaysia1 varieties before transplanted into the field, and the efficacy of eCO2 to improve rice harvest components in both varieties. The study used a novel approach where the rice plants were treated with high CO2 only during their early vegetative stage before being transplanted into the field. The source of CO2 for eCO2 condition was obtained from baker’s yeast fermentation which was 600 to 800 μmol mol-1, for the ambient CO2 (aCO2) it was 410 μmol mol-1 to 415 μmol mol-1 and control at field condition. Rice seedlings were grown in a nested design with 15 replication for four weeks in a growth chamber under LED lights (white, red, and blue. The seedlings in the control treatment were grown in the field. After four weeks, the seedlings grown in growth chambers were transplanted to the field and arranged in a rain shelter in a two factorial randomized complete block design (RCBD) with four blocks. Leaf properties of rice seedlings, for instance, leaf length, leaf number per plant, and leaf area were increased by 9.20%, 10.28%, and 25.67% respectively in eCO2 compared to control. Similarly, general growth properties were also increased, such as seedling height was increased by 18.25% and seedling dry weight by 34.21% under eCO2 compared to control. Moreover, results from the field experiment also demonstrated that the growth properties of rice such as plant height and plant dry weight were also increased in the eCO2 compared to the control by 5.29% and 43.84%, respectively. Tiller-panicle properties also increased in eCO2 treatment than control such as tiller number per plant, panicle number per plant, and panicle length that increased by 18.38%, 20.96%, and 14.15%, respectively. The non-productive tiller number per plant was also decreased by 30.53%. Moreover, rice grain properties also demonstrated significant improvement under eCO2 conditions compared to control. Filled grain per panicle and grain yield was increased by 15.30% and 47.48%, respectively. The non-filled grain per panicle was decreased by 42.04% under eCO2 conditions compared to control. In conclusion, this experiment has demonstrated that eCO2 treatment on rice seedlings enhanced seedling and plant growth, as well as grain yield of rice. This study suggested that temporary eCO2 treatment on rice seedlings has the potential to enhance rice production thus can help farmers to earn a higher income and improve their living standard.